Effect of different durations of using a standing frame on the rate of hip migration in children with moderate to severe cerebral palsy: a feasibility study for a randomised controlled trial. (September 2022) - Rapson, R.; King, T.; Morris, C.; Jeffery, R.; Mellhuish, J.; Stephens, C.; Marsden, J.
Abstract: Aim: To assess the feasibility of a randomised controlled trial (RCT) to evaluate the effect of different doses of standing time on hip migration rate in children with cerebral palsy (CP). Method: Children aged 1–12 years with CP GMFCS levels III–V were recruited and randomised to either doubling or continuing with their usual time in their standing frame. Caregivers kept a standing time diary. The primary outcome measure was Reimers hip migration percentage, measured at baseline, 12 and 24 months. A blinded assessor measured secondary clinical outcomes at baseline, 6 and 12 months. Feasibility results are reported following CONSORT guidelines. Results: Twenty-five children were recruited. Nineteen were randomised and 10 completed the 12-month intervention. The mean daily standing time in the intervention group was 49 minutes (SD 39.1) (Monday–Sunday) and 58.1 (SD 44.1) minutes during weekdays. In children remaining in the trial, primary and secondary clinical outcome measures were available in 54% and 90% of children respectively. There were three serious adverse events, unrelated to standing. Conclusions: It may be feasible to conduct an RCT to assess the effect of duration of standing on hip migration in children with CP with an altered protocol. The suggested target dose is 60 minutes five times per week compared to a control group standing for 30 minutes three times per week, over twelve months. Use of botulinum toxin need not be a criterion for exclusion and radiography should be included as a research cost. NHS Health Research Committee, South West ethics approval (ref 13/SW/0228).